2011
DOI: 10.1007/s00425-011-1364-5
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of a protein kinase in phototaxis and gravitaxis of Euglena gracilis

Abstract: The unicellular flagellate Euglena gracilis shows positive phototaxis at low-light intensities (<10 W/m(2)) and a negative one at higher irradiances (>10 W/m(2)). Phototaxis is based on blue light-activated adenylyl cyclases, which produce cAMP upon irradiation. In the absence of light the cells swim upward in the water column (negative gravitaxis). The results of sounding rocket campaigns and of a large number of ground experiments led to the following model of signal perception and transduction in gravitaxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 21 publications
0
45
0
Order By: Relevance
“…The protists Paramecium (ciliate) and Euglena (flagellate) show distinct gravity-guided modes of behavior in the form of negative gravitaxis (orientation against the direction of the gravity vector) and gravikinesis (regulation of the swimming speed with respect to the swimming direction) (Machemer et al, 1991;Machemer and Brä ucker, 1992;Lebert and Hä der, 1996;Hä der et al, 2005aHä der et al, , 2005bHä der et al, , 2006Hä der et al, , 2010Hemmersbach and Braun, 2007;Daiker et al, 2011). Studies in real microgravity have demonstrated the loss of these responses in a time frame of 1-2 min (Hemmersbach-Krause et al, 1993a, 1993bHemmersbach et al, 1996aHemmersbach et al, , 1996bHä der et al, 2005a).…”
Section: Paramecium and Euglena-unicellular Free-swimming Cellsmentioning
confidence: 99%
“…The protists Paramecium (ciliate) and Euglena (flagellate) show distinct gravity-guided modes of behavior in the form of negative gravitaxis (orientation against the direction of the gravity vector) and gravikinesis (regulation of the swimming speed with respect to the swimming direction) (Machemer et al, 1991;Machemer and Brä ucker, 1992;Lebert and Hä der, 1996;Hä der et al, 2005aHä der et al, , 2005bHä der et al, , 2006Hä der et al, , 2010Hemmersbach and Braun, 2007;Daiker et al, 2011). Studies in real microgravity have demonstrated the loss of these responses in a time frame of 1-2 min (Hemmersbach-Krause et al, 1993a, 1993bHemmersbach et al, 1996aHemmersbach et al, , 1996bHä der et al, 2005a).…”
Section: Paramecium and Euglena-unicellular Free-swimming Cellsmentioning
confidence: 99%
“…An explanation for the cessation of upward movement and subsequent (slower) decrease in surface biomass would be that cells stop responding to gravity (Coelho et al, 2011). These results could also be explained by a 'gravity sign change', as observed for the flagellate Euglena gracilis (Daiker et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…Some microalgae can reorient themselves with respect to gravity by using the whole protoplast as a sedimenting body. In the well-studied case of Euglena gracilis, gravisensing is based on a transduction chain triggered by the higher density of the protoplast in relation to the surrounding medium, the resulting pressure on the lower part of the cell membrane, subsequent activation of mechano-sensitive ion channels and a change in the cytosolic calcium concentration and membrane potential (Häder, 1999;Hemmersbach et al, 1999;Daiker et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we successfully described the population statistics, on the single cell level the mechanism of the active fluctuations and of the observed "fatigue" remains unclear. This mechanism can be investigated further if one addresses complex and not fully understood impulse-response behaviors involving the photoactivated adenylyl cyclase [39,50] and protein kinase [51].…”
Section: Discussionmentioning
confidence: 99%